2006
DOI: 10.1029/2006gl026316
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the South China Sea throughflow inferred from wind data and an ocean data assimilation product

Abstract: The Luzon Strait transport, as an index for the South China Sea throughflow, has attracted much attention recently. In this study the interannual variability of Luzon Strait transport is examined, using the Island Rule and results from ocean data assimilation. Transport variability obtained from these two approaches is consistent with each other. Assessment of contribution from each integral segment involved in the Island Rule indicates that wind stress in the western and central equatorial Pacific is the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 16 publications
7
95
0
1
Order By: Relevance
“…The variability of SCSTF is mainly controlled by the equatorial Pacific wind stress on the interannual time scale [93]. The SCSTF increased and the ITF decreased after the 1976/77 climate shift [105], which is similar with their variations on interannual time scales [106].…”
Section: Implication Of the Scs Throughflow (Scstf)supporting
confidence: 63%
See 1 more Smart Citation
“…The variability of SCSTF is mainly controlled by the equatorial Pacific wind stress on the interannual time scale [93]. The SCSTF increased and the ITF decreased after the 1976/77 climate shift [105], which is similar with their variations on interannual time scales [106].…”
Section: Implication Of the Scs Throughflow (Scstf)supporting
confidence: 63%
“…The Pacific water entering the SCS through the Luzon Strait can flow southward along the western boundary, and will re-enter into the Pacific as a surface current in the Makassar Strait after flowing out of the SCS through the Karimata Strait, which plays an important role to the heat transport of the ITF on the interannual time scale [92]. This circulation branch in the SCS connecting the Pacific and Indian oceans, which originates from the western Philippine Seas toward the Indonesian Seas through the SCS, as well as through the Karimata and Mindoro straits, is named as the SCSTF [93].…”
Section: Implication Of the Scs Throughflow (Scstf)mentioning
confidence: 99%
“…The SCS is a semi-closed basin below about 200 m. On the longterm average this heat and freshwater gain can only be balanced by horizontal advection, with inflow of cold and salty water through the Luzon strait and outflow of warm and fresh water through the Mindoro and Karimata straits. This circulation has been termed as the South China Sea throughflow (SCSTF) Wang et al 2006). The South China-Indonesian Seas Transport/Exchange (SITE) program in 2007-2016 measured the SCSTF in the Karimata and Sunda Strait (Fang et al 2010;Susanto et al 2013).…”
Section: Sources and Pathways Of The Itf Watermentioning
confidence: 99%
“…The changes in ocean circulation and sea level associated with the monsoons are identified as the primary forcing mechanism of the SCSTF seasonal variability (Metzger and Hurlburt 1996). Meanwhile, its inter-annual as well as decadal variability are considered to be mainly governed by the ENSO Phenomenon (e.g., Qu et al 2004;Wang et al 2006b;Liu et al 2012). However, recent studies revealed that other large-scale phenomena such as the PDO also have a significant role in determining the low-frequency variability of the SCSTF (Yu and Qu 2013;Nan et al 2015).…”
mentioning
confidence: 99%